Experience of Pandemic Influenza A (H1N1) 2009 at Dhaka Medical College Hospital (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v28i1.4648 J Bangladesh Coll Phys Surg 2010; 28: 63